The use of Remote Sensing Technology in geological Investigation and mineral Detection in El Azraq-Jordan - Samih Al-Rawashdeh; Bassam Saleh; Mufeed Hamzah (Cybergeo, 2006)
This study examines the use of Remote Sensing (RS) technology in geological studies in El Azraq area. LandSat Enhanced Thematic Mapper plus (ETM+) and Radar SAR images were used to (i) classify the various geological units found in El Azraq area located in the North-East of Jordan, (ii) discriminate the lithology and structure of this area, and (iii) delineate the associated zones of hydrothermal alteration. A wide variety of digital image processing techniques were applied such as the Principal Components (PC) analysis, ratioing and Intensity, Hue and Saturation (IHS) transformation. The color composite of Principal Components (1, 2, and 3), the ratio images (3/1, 4/3, and 5/7) and the IHS (1, 3, 5) enabled us to determine the different types of igneous rocks in the study area. A remote sensed lineament map was produced using two different methods: (i) application of directional filters and edge enhancement; and (ii) data fusion of ETM+ with SAR image. The selective PC analysis of ETM+ using bands 1, 3, 4, and 5 was used in mapping iron and iron oxide bearing minerals. The same method was also applied using bands 1, 4, 5, and 7 for hydroxyl bearing minerals detection. Finally, the hyper spectral technique was used for detecting the different minerals in the study area based on the spectral library of minerals.